Analysis of movement and actions of wingers as second-line players in organized attack in handball - Hatzimanouil, D.; Saavedra, J. M.; Lola, A.; Skandalis, V.; Gkagkanas, K. (Journal of Human Kinetics, 2024)
In modern handball, one of the important performance indicators is the effectiveness of the attack, especially the running-in of wingers as line players which has not been explored adequately. The purpose of the study was to analyze the movements of wingers in the organized attack when they run in. Fifty-eight matches were analyzed from the 2022 EHF European Men`s Handball Championship. A total of 491 attacks were recorded and 45 variables were analyzed in which wingers ran in as second pivots and the outcome was a throw. For the statistical analysis, descriptive and inductive statistics were used. The results showed that the average time of the running-in was 12.11 ± 9.28 s, the left wing ran in more often (60.1%) and wingers tended to move outside the defense formation (72.5%). Wingers ran in without the ball in possession (81.1%), moved toward defenders 2 and 5 and stood next to defenders, and occasionally blocked, slid or left their position. The defense`s central zone was preferred by players to make a throw. Correspondence analysis showed that wingers finally returned to their initial position regardless of the evolution of the attack. Their role was to block a specific defender or disorganize the defense, for one defender to be isolated so that one attacking player could execute a shot from the central area. Conclusively, wingers play an important role, especially in run-in actions, at the completion of an attack, and in the final throw.